Karawo Art as a Cultural Pedagogy: Exploring the Role of Embroidery in Fostering Cultural Identity and Contextual Learning - Mursidah Waty; Soesanto; Eko Haryanto; Eko Sugiarto (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Traditional arts often face challenges in maintaining their relevance within modern curricula that are more oriented toward academic achievement. This study aims to analyze and evaluate the role of Karawo art as cultural pedagogy in strengthening identity, fostering creativity, and enhancing students’ social skills. The research employs a qualitative descriptive method with an ethnographic approach. The study involved 17 informants selected through purposive sampling, consisting of 3 artists, 3 Karawo craftsmen, 3 teachers, 6 students, and 2 policymakers. Data were collected through semi-structured in-depth interviews, participant observation in classrooms and community-based activities, as well as document analysis, including curricula, lesson plans, photographs, and videos. The research instruments included interview guidelines, observation sheets, and document analysis forms. Data were analyzed qualitatively through transcription, data reduction, descriptive narrative presentation, as well as thematic and content analysis to identify patterns, themes, and conceptual relationships. The findings reveal that the integration of Karawo art in learning varies, with the main challenges being limited instructional time, teachers’ competencies, and students’ readiness. Nevertheless, The study concludes that Karawo art plays a strategic role as cultural pedagogy relevant to modern education. The implications highlight the importance of developing culture-based curricula, enhancing teachers’ capacities, and strengthening collaboration between schools, communities, and local governments to support cultural preservation through education.